Educational Neuroscience and Teachers' Perspectives on Pedagogy: A Critical Review of Pro, Con, and Neutral Perspectives - Rizki Eka Putra; Budi Budi; Silvia Marlina; Moh. Arief Hidayat; Yuharniza Yuharniza; Julhadi Julhadi; Ahmad Sabri (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
With the growing interest in neuroscience application to education, neuroscience is now considered as an interdisciplinary approach to understanding the learning processes from the brain science perspective. However, its use in education has been contested because of the dangers of reductionism and neuromyths, and the lack of relevance of neuroscientific findings to classroom practice. The study seeks to critically examine the pro, counter and neutral positions on the integration of neuroscience in education and to identify a more balanced framework for its implementation. This study used a critical literature review method. The research data were obtained from 18 articles selected from 2018 to 2026 obtained from Scopus, Web of Science, and Google Scholar databases. The data were thematically analyzed to categorize arguments into three major perspectives: pro, counter, and neutral. The results suggest that the pro perspective highlights neuroscience as a scientific basis for evidence-based pedagogy whereas the counter perspective highlights risks of biological reductionism, neuromyths and loss of teacher autonomy. Meanwhile, the neutral perspective sees neuroscience as a contextual tool that should be critically integrated with educational theory and sociocultural realities. The scientific contribution of this article is the construction of a critical realist framework that reconciles competing perspectives, and repositions teachers as reflective practitioners mediating between scientific knowledge and pedagogical practice. The study concludes that the inclusion of neuroscience in education requires interdisciplinary, contextual and ethically grounded approaches to avoid simplification and strengthen meaningful learning practices.